2019
DOI: 10.1177/0022022118823283
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Mental State Reading Ability in Antillean Dutch, Moroccan Dutch, and Dutch Young Adults

Abstract: Understanding how bicultural and monocultural individuals are oriented toward the cultures they come into frequent contact with can increase insights into their adaptation and wellbeing. Previous research has shown a relation between culture and mental state reading in the form of the cultural in-group effect, which is defined as the advantage in reading mental states from the own cultural group compared with other groups. Thus, orientation toward cultures can be assessed not only in self-reported behavioral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…x, y, and z of the Montreal Neurological Institute (MNI) coordinates in the left-right, anterior-posterior, and inferior-superior dimensions, respectively. www.nature.com/scientificreports/ culture RMET and the Caucasian RMET, while Caucasian Dutch individuals performed worse on the other cultures' RMETs 9 . The authors of this study suggested that bicultural individuals need to adjust to the Dutch (majority) culture in situations such as work or school, while during interactions with their relatives, they still need to act according to their primary culture.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…x, y, and z of the Montreal Neurological Institute (MNI) coordinates in the left-right, anterior-posterior, and inferior-superior dimensions, respectively. www.nature.com/scientificreports/ culture RMET and the Caucasian RMET, while Caucasian Dutch individuals performed worse on the other cultures' RMETs 9 . The authors of this study suggested that bicultural individuals need to adjust to the Dutch (majority) culture in situations such as work or school, while during interactions with their relatives, they still need to act according to their primary culture.…”
Section: Discussionmentioning
confidence: 93%
“…The increased activation of the pSTS when understanding the mental states of children might reflect the increased importance of such interactions in the WC group. The increased importance of these interactions was previously proposed as being responsible for the ability of teachers to better remember children's faces 17 and for better performance in RMETs of other cultures 9 . The other explanation would simply be a better ability to process sensory information derived from the eye region, in other words, sensory expertise caused by familiarity.…”
Section: Contrastmentioning
confidence: 96%
See 3 more Smart Citations